The wise team coach : crafting a personal approach to team coaching - Lawrence, Paul, 1963- (Routledge, 2025)
"Based on three years of meta-research into team effectiveness and coaching, this book explores some of the most common contradictions and debates around the topic of team coaching and presents readers with a framework to enable them to explore this field for themselves, reflecting on their own experience and drawing their own conclusions. Team coaching in organisations is still a relatively new discipline, with industry associations having only recently defined their first attempts to frame team coaching in the form of standard skills and competencies. As a new discipline we still see multiple perspectives on what team coaching is, and how it should best be practiced. The literature abounds with paradox and contradictions. Within this book Lawrence delves into these contradictions and debates, providing a framework to encourage readers to construct their own practice model. Covering both theory and practical application, this will be a useful guide for both experienced team coaches and those entering the field"-- Provided by publisher.
Keywords: Employees -- Coaching of.; Teams in the workplace -- Management.; Organizational behavior.; Executive coaching.; elektronické knihy; electronic books